Normal resting electrocardiographic variants in young athletes - Higgins, J. P. (The Physician and Sportsmedicine, 2008)
Abstract: With a growing awareness of the tragedy of sudden cardiac arrest (SCA) in young athletes, more extensive pre-participation examinations are being performed prior to competitive sport participation. In addition to a history and physical, young athletes often have a 12-lead resting electrocardiogram (ECG) to better identify heart disease associated with SCA. Complicating this process is that certain "abnormal" resting ECG findings are considered normal variants in healthy children and young adults. The ability to recognize these normal variants is often useful in preventing excessive referral of patients to cardiologists for evaluation of resting ECG's that are benign variations of normal and in making sound decisions regarding appropriate clearance to exercise. This review describes these normal variants.